PERLINDUNGAN HUKUM TERHADAP HAK MANTAN NARAPIDANA - Cahyono, Rudi (JUSTNESS - Jurnal Hukun dan Agama, 2023)
Abstrack Human right are basic rights or citizenship inherent in individuals from the time they are born wich cannot be deprived and revoked of their existence and must be respected, upheld, and protected by the state and law. Likewise for ex-convicts to get to job and a decent living. The purpose of this study is to find out Law Number 39 of 1999 which regulates the protection of human rights for ex convicts to get a decent job and livelihood, and to find out why ex-convicts are discriminated against in the right to get a decent job. The research method used is normative juridical with a qualitative approach, namely by collecting and utilizing information related to this research. The results of this study indicate that the rights of former prisioners to get a decent job and life are regulated in Law Number 39 of 1999 concerning human rights, Article 38 Paragraph (1) concerning decent Work and Article 40 cncerning a decent life. Keywords : human rights and ex-convict